OʻTKIR HOSHIMOVNING “IKKI ESHIK ORASI” ROMANIDA INSON TAQDIRI VA URUSH FOJEASI MUAMMOSINING BADIIY-FALSAFIY TALQINI - Xoliqova Lobar Otajon qizi (International Journal of Literature and Language Studies, 2026)
This article provides a comprehensive analysis of the novel "Between Two Doors" (Ikki eshik orasi) by the prominent Uzbek writer Oʻtkir Hoshimov, based on the criteria of modern literary criticism. The study examines the social and psychological life of the Uzbek people during the Second World War and the post-war years, the evolution of the characters' personalities, and the philosophical-mythological roots of the "between two doors" concept. Furthermore, the nature of polyphony (multivoicedness), the problem of chronotope (space and time), artistic psychologism, and the principles of symbolism in the novel are scientifically substantiated through comparative-analytical methods.